2013
DOI: 10.12720/lnit.1.2.77-82
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Adhoc Sensor Network Framework to Provide Green Communication for Urban Operation Rescue

Abstract: The use of wireless technology based on vehicle ad hoc network and wireless sensor network may give opportunity to the operational rescue team for emergency cases. Information transmitted using the vehicular and sensor technologies may improve the rescue communication. In this paper, a green communication framework is proposed to support the operation rescue together with green communication requirements. The proposed model is validated using two parameters which are average packet delivery ratio and level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…With IoT technology at each stage of the supply chain, it introduces potential cybersecurity threats since a security breach in just-in-time distribution system could also have a serious cascading effects on the entire supply chain. The massive scale of attacks like Wan-naCry 27 ransomware, and the recent spate of ransomwares in cities 28 across the US, suggest that even a breach or data freeze at a single inter-dependent entity will be enough to disrupt the whole chain and possibly the economy of a country.…”
Section: Supply Chain Attacksmentioning
confidence: 99%
See 1 more Smart Citation
“…With IoT technology at each stage of the supply chain, it introduces potential cybersecurity threats since a security breach in just-in-time distribution system could also have a serious cascading effects on the entire supply chain. The massive scale of attacks like Wan-naCry 27 ransomware, and the recent spate of ransomwares in cities 28 across the US, suggest that even a breach or data freeze at a single inter-dependent entity will be enough to disrupt the whole chain and possibly the economy of a country.…”
Section: Supply Chain Attacksmentioning
confidence: 99%
“…Extensive research on secure IoT devices [13]- [15], smart vehicles [16]- [19], drones [20], [21], edge cloud [22]- [24], wireless communication [25]- [27] is already available and might be extended to the smart farming ecosystem. However, most of the time, research is conducted on these technologies without consideration of the environment they are used.…”
Section: Introductionmentioning
confidence: 99%
“…The link gain matrix assumes that all the drivers drive with good behavior, which means all the nodes keep the same speed with the front node when they are following; hence the Doppler shifting effect is considered as zero. The simulation has been completed in MATLAB based on the developing tool for power control game [4].…”
Section: Simulationmentioning
confidence: 99%
“…It is reported that over 3% energy of global range is consumed by Information and Communication Technology (ICT), and such energy consumption will increase continuously in the future [4]. Transmission power, especially, has crucial impacts on enhancing the throughput of wireless communication.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CO 2 and greenhouse gases emissions can be decreased by providing smooth trips which include fewer stop and go driving state as well as lesser stopping times. Hence finding effective solutions with reasonable cost for congestion mitigation can reduce the fuel consumption and minimize the pollutant emission and preserve the environment clean and green (Salvi et al (2013); Ahmed et al (2013); Bakhouya et al (2011)). …”
Section: Introductionmentioning
confidence: 99%